2021
DOI: 10.21037/sci-2020-029
|View full text |Cite
|
Sign up to set email alerts
|

Novel progresses of chimeric antigen receptor (CAR) T cell therapy in multiple myeloma

Abstract: Multiple myeloma (MM) is a malignant proliferative disease of plasma cells, which leads to suppressed hematopoietic and osteolytic diseases. Despite the use of traditional chemotherapy, hematopoietic stem cell transplantation (HSCT) and targeted drugs, MM still cannot be completely cured. In recent years, chimeric antigen receptor (CAR) T cells have revolutionized immunotherapy and cancer treatment. The great success of CAR-T cells in leukemia and lymphoma has promoted its development in MM. The primary requis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 62 publications
(47 reference statements)
0
13
0
Order By: Relevance
“…Chimeric antigen receptor T (CAR-T) cells, which are genetically modified T cells harvested from patients to express special CARs, target tumor cells and can produce remissions again for patients who are resistant to standard therapies (1). CAR-T cell therapy has demonstrated inspiring efficacy in the treatment of B-cell original malignancies and its scope of application is broadening to many other malignancies even to solid cancers (2)(3)(4)(5)(6). Nevertheless, despite its promising efficacy, adverse events such as cytokine-release syndrome (CRS), immune effector cell-associated neurotoxicity syndrome (ICANS), cytopenia and B-cell aplasia have limited the application of CAR-T cell therapy (7).…”
Section: Introductionmentioning
confidence: 99%
“…Chimeric antigen receptor T (CAR-T) cells, which are genetically modified T cells harvested from patients to express special CARs, target tumor cells and can produce remissions again for patients who are resistant to standard therapies (1). CAR-T cell therapy has demonstrated inspiring efficacy in the treatment of B-cell original malignancies and its scope of application is broadening to many other malignancies even to solid cancers (2)(3)(4)(5)(6). Nevertheless, despite its promising efficacy, adverse events such as cytokine-release syndrome (CRS), immune effector cell-associated neurotoxicity syndrome (ICANS), cytopenia and B-cell aplasia have limited the application of CAR-T cell therapy (7).…”
Section: Introductionmentioning
confidence: 99%
“…And Friedman et al found that the expression level of BCMA on malignant plasma cells of MM patients is heterogeneous (14). Because of its restricted expression pattern and physiological function, BCMA is really an ideal target for MM CAR-T therapy (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Anti-CD38 monoclonal antibodies such as daratumumab, have been approved by the FDA for the treatment of newly diagnosed MM (30) and relapsed/refractory MM (31). Compared with anti-CD38 monoclonal antibodies, CD38 CAR-T cells have substantially improved specificity and can induce a durable and efficient response (32). Although CD38 CAR-T cells targeting MM have been reported, there are still no approved CD38 CAR-T cell products for clinical use; thus, more novel CD38 CAR-T cell clinical treatments are needed to advance the treatment of hematological cancers.…”
Section: Discussionmentioning
confidence: 99%